Evaluación de los efectos del biocarbón como enmienda edáfica en la fitosanidad del cultivo de cacao tipo nacional - Farez Yunga, Dayse Veronica (Machala : Universidad Técnica de Machala, 2020)
The productivity of a cocoa plantation is affected by pests and diseases, generating considerable losses because they affect fruits of different ages, which has caused the replacement of National cocoa plantations with CCN-51 cocoa recognized for its high production and resistance to pests and diseases, however, the quality in terms of flavor and aroma is low, if it is not given a good post-harvest process to benefit the grain. The main objective of this work was to evaluate the effect of different organic amendments applied in an edaphic way on the phytosanitary nature of the national type cocoa crop. The experimental field trial was developed at the “Palenque” farm located in the Pejeyacu sector, Cantón Chilla. A randomized block design was used with 7 treatments and 10 repetitions per treatment, the study variables were total number of ears per plant, number of healthy ears per plant, number of diseased ears per plant, number of ears harvested per plant, weight of ear, number of kernels per ear, weight of 100 fresh kernels, weight of 100 dry kernels, pest severity index, disease index. The seven treatments evaluated were: (T1) biochar and chicken manure, (T2) biochar, Fossil Shell Agro and chicken manure, (T3) biochar, Fossil Shell Agro and chicken manure, (T4) Fossil Shell Agro and chicken manure, (T5) calcium silicate and chicken manure, (T6) agricultural lime, biochar and chicken manure, (T7) Control. The biochar was obtained from the burning of diseased ears in the furnace of Mr. Carlos Ramón's farm in Rio Negro, later it was crushed to pulverize it, then the treatments were weighed separately and then applied to the plants, we drilled the soil with the help of a hercules around the plants and it was applied in a circular way at a distance of 50 cm, then it was covered with litter. Applications were made every month for six months. The harvest was carried out when three months had elapsed after having finished with the application cycle of the treatments, this coincided with the time in which the pods take from flower to harvest in the degree of organoleptic maturity. For the harvest, pruning shears were used with the aim of not causing damage to the flower bearings, the harvest data was taken in situ. For the statistical analysis the SPSS program was used. The results show that the variable total number of ears in T1, T2 and T3 were the best. T1 had a higher number of healthy ears. From T1 to T5 more ears were harvested. The T1 and T3 registered a higher weight of ear. The T3 was maintained with a higher number of almonds per treatment. Treatments T1 and T6 had a higher weight of wet seeds. T5 presented a higher weight of dry seeds. T4 and T5 were the least affected by pests while T2 was the least affected by diseases. The application of Fossil Shell plus chicken manure showed a lower percentage of pest index and the dose of 100 grams of biochar in combination Fossil Shell and chicken manure obtained a lower index of diseases. By applying 100 grams of biochar and chicken manure, he obtained an increase in the production of fruits per treatment. The weight of the ear and the number of almonds was higher with the application of 50 grams of biochar in combination with Fossil Shell plus chicken manure.
La productividad de una cacaotera se ve afectada por plagas y enfermedades generando pérdidas considerables debido a que afectan a frutos de diferentes edades, lo que ha ocasionado el reemplazo de plantaciones de cacao Nacional por cacao CCN-51 reconocido por su alta producción y resistencia a plagas y enfermedades, no obstante, la calidad en cuanto a sabor y aroma es baja, si no se le da un buen proceso de poscosecha de beneficio del grano. El objetivo principal de este trabajo fue evaluar el efecto de diferentes enmiendas orgánicas aplicadas de forma edáfica en la fitosanidad del cultivo cacao tipo nacional. El ensayo experimental de campo se desarrolló en la finca “Palenque” ubicada en el sector Pejeyacu, Cantón Chilla. Se utilizó un diseño de bloques al azar con 7 tratamientos y 10 repeticiones por tratamiento, las variables de estudio fueron número total de mazorcas por planta, número de mazorcas sanas por planta, número de mazorcas enfermas por planta, número de mazorcas cosechadas por planta, peso de mazorca, número de almendra por mazorca, peso de 100 almendra frescas, peso de 100 almendras secas, índice de severidad plagas, índice de enfermedades. Los siete tratamientos evaluados fueron: (T1) biocarbón y gallinaza, (T2) biocarbón, Fossil Shell Agro y gallinaza, (T3) biocarbón, Fossil Shell Agro y gallinaza, (T4) Fossil Shell Agro y gallinaza, (T5) silicato de calcio y gallinaza, (T6) cal agrícola, biocarbón y gallinaza, (T7) Testigo. El biocarbón se obtuvo de la quema de mazorcas enfermas en el horno de la finca del señor Carlos Ramón en Rio Negro posteriormente se procedió a triturarlo hasta pulverizarlo, luego se pesó los tratamientos por separado para después ser aplicado en las plantas, perforamos el suelo con la ayuda de un hércules alrededor de las plantas y se aplicó en forma circular a una distancia de 50 cm posteriormente se procedió a cubrir con hojarasca. Las aplicaciones se realizaron cada mes durante seis meses. La cosecha se efectuó cuando habían pasado tres meses de haber terminado con el ciclo de aplicaciones de los tratamientos, esto coincidió con el tiempo en que demoran las mazorcas desde flor hasta la cosecha en grado de madurez organoléptica. Para la cosecha, se utilizó tijeras de podar con el objetivo de no causar daños en los cojinetes florales, se tomaron los datos de cosecha in situ. Para el análisis estadístico se utilizó el programa SPSS. Los resultados demuestran que la variable número total de mazorcas en el T1, T2 y T3, fueron los mejores. El T1 tuvo un mayor número de mazorcas sanas. Del T1 al T5 se cosecharon más mazorcas. El T1 y T3 registraron un mayor peso de mazorca. El T3 se mantuvo con un mayor número de almendras por tratamiento. Los tratamientos T1 y T6 presentaron mayor peso de semillas húmedas. El T5 presentó mayor peso de semillas secas. El T4 y T5 fueron los menos afectados por plagas mientras que el T2 fue el menos afectado por enfermedades. La aplicación Fossil Shell más gallinaza demostró un menor porcentaje de índice de plagas y la dosis de 100 gramos de biocarbón en combinación Fossil Shell y gallinaza obtuvo menor índice de enfermedades. Al aplicar 100 gramos de biocarbón y gallinaza obtuvo un aumento en la producción de frutos por tratamiento. El peso de la mazorca y el número de almendras fue mayor con la aplicación de 50 gramos de biocarbón en combinación con Fossil Shell más gallinaza.
Keywords: CACAO; NACIONAL; BIOCARBÓN; GALLINAZA